Developing a tool to measure health worker motivation in district hospitals in Kenya - Gilson Lucy; Blaauw Duane; Mbindyo Patrick M; English Mike (BMC, 2009)
Abstract Background We wanted to try to account for worker motivation as a key factor that might affect the success of an intervention to improve implementation of health worker practices in eight district hospitals in Kenya. In the absence of available tools, we therefore aimed to develop a tool that could enable a rapid measurement of motivation at baseline and at subsequent points during the 18-month intervention study. Methods After a literature review, a self-administered questionnaire was developed to assess the outcomes and determinants of motivation of Kenyan government hospital staff. The initial questionnaire included 23 questions (from seven underlying constructs) related to motivational outcomes that were then used to construct a simpler tool to measure motivation. Parallel qualitative work was undertaken to assess the relevance of the questions chosen and the face validity of the tool. Results Six hundred eighty-four health workers completed the questionnaires at baseline. Reliability analysis and factor analysis were used to produce the simplified motivational index, which consisted of 10 equally-weighted items from three underlying factors. Scores on the 10-item index were closely correlated with scores for the 23-item index, indicating that in future rapid assessments might be based on the 10 questions alone. The 10-item motivation index was also able to identify statistically significant differences in mean health worker motivation scores between the study hospitals (p < 0.001). The parallel qualitative work in general supported these conclusions and contributed to our understanding of the three identified components of motivation. Conclusion The 10-item score developed may be useful to monitor changes in motivation over time within our study or be used for more extensive rapid assessments of health worker motivation in Kenya.